Offshoring, domestic outsourcing, and productivity: Evidence for a number of European countries - Tillmann Schwörer (Kiel Institute for the World Economy (IfW), 2012)
The economic effects of offshoring have been subject to extensive empirical analysis in the past, but many studies have not accurately distinguished between offshoring, domestic outsourcing, and the substitution of domestic by foreign suppliers. In this study I provide stylized facts on offshoring in Europe between 1995 and 2008 taking into account this distinction. I show that service inputs have been offshored and domestically outsourced, whereas material inputs have been either offshored or moved from domestic to foreign suppliers. The strong overall decline in the share of internal production evokes the question whether this has led to productivity gains within firms. I address this question by combining industry-level data on offshoring and domestic outsourcing with a firm panel. I find that offshoring of non-core activities has led to productivity gains whereas offshoring of core activities and domestic outsourcing have had no such effects. The estimated productivity gains are in particular driven by offshoring to low-wage countries and by the gains of multinational firms.
Keywords: F23; D24; L24; L60; 330; offshoring; domestic outsourcing; productivity; Auslandsverlagerung; Outsourcing; Unternehmensdienstleistung; Vorprodukt; Materialwirtschaft; Produktivität; Schätzung; Europa